2017
DOI: 10.1111/cei.12905
|View full text |Cite
|
Sign up to set email alerts
|

RORγt expression in Tregs promotes systemic lupus erythematosus via IL-17 secretion, alteration of Treg phenotype and suppression of Th2 responses

Abstract: Systemic lupus erythematosus (SLE) is a common autoimmune disorder with a complex and poorly understood immunopathogenesis. However, a pathogenic role for the T helper type 17 (Th17) axis was demonstrated by many studies, while regulatory T cells (T ) were shown to mediate protection. Recently, we and others characterized a novel and independent T cell population expressing both the T characteristic transcription factor forkhead box protein 3 (FoxP3) and the Th17-defining retinoic acid receptor-related orphan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 46 publications
4
32
0
Order By: Relevance
“…The orphan retinoid receptor, RORc, which is the master transcription factor in IL-17-secreting cells, appears to be required for IL-17 production. 24,25 Transduction of naive T cells with RORc induces the development of IL-17-secreting cells. 26,27 In addition, activation of STAT3 is necessary to induce RORc and induce expression of IL-17 by increasing the expression of RORc.…”
Section: Discussionmentioning
confidence: 99%
“…The orphan retinoid receptor, RORc, which is the master transcription factor in IL-17-secreting cells, appears to be required for IL-17 production. 24,25 Transduction of naive T cells with RORc induces the development of IL-17-secreting cells. 26,27 In addition, activation of STAT3 is necessary to induce RORc and induce expression of IL-17 by increasing the expression of RORc.…”
Section: Discussionmentioning
confidence: 99%
“…15,22 In the pathological environment, Foxp3 + IL-17 + T cells mainly play a pro-inflammatory role. [22][23][24] In research studies, intravenous immunoglobulin G treatment and lymphocyte immunotherapy have commonly been applied to modulate the Treg/Th17 imbalance in pregnant women with RPL. [25][26][27] In a study using an abortion-prone mouse model, transfer of pregnancyinduced CD4 + CD25 + Treg cells was able to reverse the elevated abortion rate which was induced by IL-17.…”
mentioning
confidence: 99%
“…Depletion studies in pristane‐induced models of lupus nephritis have demonstrated that endogenous Stat3‐expressing Foxp3 + Tregs (‘Treg17’) afford protection from injury, as Foxp3‐Cre deletion of Stat3 led to heightened Th17 responses and less Treg17 cell recruitment to the kidney, likely due to impaired CCR6 expression . The same group showed that in the same model, Foxp3 + RORγt + Tregs (‘biTregs’) were pathogenic, at least in part, because RORγt induce the secretion of IL‐17 in biTreg cells …”
Section: Regulatory T Cells In Autoimmune Glomerulonephritismentioning
confidence: 99%
“…37 The same group showed that in the same model, Foxp3 + RORct + Tregs ('biTregs') were pathogenic, at least in part, because RORct induce the secretion of IL-17 in biTreg cells. 38 A number of treatments in several murine models of lupus have been associated with increased Treg number or function, including, in MRL/lpr strain, IL-33 inhibition, piperlongumine and the 4hydroxyquinoline-3-formamide derivative (known as Y27) [39][40][41] ; in NZBxW/F1 mice, IL-2/IL-2 mAb immune complexes, G-CSF and tuftsin-phosphorylcholine [42][43][44] ; and in the bm12?B6 chronic graftversus-host model of lupus nephritis, microRNA-21 deficiency. 45 Progesterone may also be important for optimal Treg number and function, as progesterone-deficient Nba2 mice have increased antichromatin IgG and proteinuria associated with a decrease in Tregs.…”
Section: Lupus Nephritismentioning
confidence: 99%